Structure–activity relationship of xanthates with different hydrophobic groups in the flotation of pyrite - Yang, X.; Albijanic, Boris; Liu, G.; Zhou, Y. (Elsevier, 2018)
Xanthate collectors have been industrially used for the flotation of pyrite in the gold mining industry because pyrite is the most common gold-bearing mineral. However, after reviewing the structure-activity relationship study of flotation collectors, the influence of hydrophobic groups on the flotation performance of collectors remains underexplored. In this paper, using density functional theory (DFT) method, the quantum chemical properties of xanthate derivatives ROC = SS-(R = ethyl, isobutyl or amyl) and their interactions with Fe3+, Fe(OH)2+, Fe(OH)2+and pyrite cluster were evaluated in the context of solvation effects. The flotation performance of substituted xanthates was experimentally investigated for a gold–pyrite ore. Based on the values of frontier orbital energies and electronic chemical potential, the flotation performance of the alkyl xanthates was predicted to be amyl xanthate > isobutyl xanthate > ethyl xanthate. The results showed that the direct chemisorption of the ferric hydroxo xanthates on the pyrite surfaces was thermodynamically possible. The flotation performance of the xanthate collectors matched with the theoretically predicted trend. This study could offer some theoretical insights into the mechanism of pyrite flotation and provide novel guidelines for rational selection/design of hydrophobic groups of flotation collectors.